Chromosome Instability and Micronucleus Frequency on the Oral Mucosa of HIV-positive Patients - Mustafa, Saifadin K. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2025)
Extranuclear structures known as micronuclei (MN) are composed of whole or fragmented chromosomes that were not incorporated into the nucleus following cell division. The genotoxic impact of HIV infection on oral cavity cancers remains uncertain. This study sought to determine the impact of HIV infection on MN in HIV+ patients’ oral mucosa and its correlation with early cytogenetic alterations in oral carcinogenesis. A total of forty-four non-HIV patients and thirty-eight HIV+ patients were assessed in this study. Smears were collected from the oral cavity and stained with 5% methylene blue. The smears were then examined at a ×100 magnification using a standard microscope. For each participant, 100 buccal cells were counted. Further observations of the viral load (VL), lymphocytes, and granulocytes were made to determine the pattern of MN presence in HIV+ patients. Significant differences were observed between HIV+ patients and healthy controls regarding alcohol consumption (p = 0.004 < 0.05) and smoking (p = 0.041 < 0.05). The relationship between micronucleus and VL is substantial. After calculating the linear regression model, it was discovered that the VL ratio of HIV-positive patients could predict the micronucleus cells (R-Sq = 55%, p < 0.000). In conclusion, HIV VL shows increased genomic instability. These findings are relevant to understanding the mechanisms of cellular damage and developing potential strategies to mitigate carcinogenesis in HIV+ patients.